A computationally rigorous approach to hybrid fire testing. (1st October 2020) - Schulthess, Patrick; Neuenschwander, Martin; Mosalam, Khalid M.; Knobloch, Markus
Highlights: Comprehensive review of state of the art reveals fundamental methodological gap. Gap filled with first computationally rigorous method for hybrid fire testing. Method validated considering all the basic physics of structural fire engineering. Scientific basis for hybrid fire testing in existing fire labs established. Abstract: Real fire incidents have shown that the structural systems of high-rise buildings perform much better during a fire attack than what classical structural fire analysis predicts. The reason behind this phenomenon is the empirically established fact that beneficial interaction mechanisms evolve between the fire-exposed and the fire-unexposed parts of structural systems. However, there is no computational method available to reliably quantify such interaction mechanisms for design purposes. Pure numerical methods are too uncertain, because they cannot be validated, and isolated structural member testing does not allow considering the interaction. Hybrid fire testing, however, can precisely fill this fundamental methodological gap when set up as an extended finite-element analysis technique. Here, we provide the first computationally rigorous method for hybrid fire testing. We have validated the novel method with several proof-of-concept tests covering the entire temperature-range relevant for structural fire engineering. In contrast to other approaches, only our method can deal, so far, at the same time suitably, accurately and robustly with the experimental and computational challenges of temperature-dependent material behavior. We therefore place hybrid fire testing on a sound scientific basis enabling existing fire test facilities to do more realistic (hybrid) assessments of the fire performance of structural systems.